Caring Behavior of Nurse Managers: A Literature Review - Permana, Bhakti; Hilmi, Nabilah (KnE Life Sciences, 2021)
The primary objective of this review was to examine the research literature for evidence about the caring behavior of Nurse Managers. After searching, we found 14 themes from five articles, then we rearranged the 14 themes into three themes of caring behavior of manager nurses. The first theme is the duty of nurse managers to improve nurse caring by coordingating nurses’ care of patients. This includes increasing continuity and accessibility of care for patients, promoting nurse’s careers professionally, supporting work balance, implementing caring behavior, and managing a caring culture. The second theme is the character of a nurse manager, such as democratic leadership, voluntary sharing, communication, respect, and feeling care. The third theme is the supporting and inhibiting factors for nurse managers such as formal organizational support, informal support from nurses, and a sense of mutual care between peers. The results suggest that nurse manager must have a strong role and character to maintain the caring culture of nurses. Keywords: caring, nurse manager, care manager, qualitative